PROSPECTIVE TEACHERS REPRESENTATIONS IN PROBLEM SOLVING OF SPECIAL ANGLE TRIGONOMETRY FUNCTIONS BASED ON THE LEVEL OF ABILITY - Yayan Eryk Setiawan (Jurnal Infinity, 2022)
One of the materials used as the basis for solving trigonometric function problems is special angle trigonometry. Prospective teachers' representation in problem-solving of trigonometric functions with special angles is thought to be influenced by prospective teachers' abilities. Therefore, this study aims to analyze the representations used by prospective teachers in problem-solving of special angle trigonometric function based on ability categories. This research is qualitative descriptive. The research subjects are prospective teachers of the mathematics education study program at a university in Malang. The data collected in this study are in the form of work results and observation. The research instrument consisted of the problem of the trigonometric function value of the special angle and the interview guide developed by the researcher. The analysis of prospective teacher work results was carried out by classifying the ability categories into low, medium, and high abilities. The work results of each of these categories are classified based on verbal, numeric, image, and algebraic representations. The analysis of the interview transcripts was carried out by coding the words or sentences which aims to determine prospective teachers' understanding of using representations. The results showed that prospective teachers with low ability use a lot of verbal representation, while prospective teachers with medium and high abilities use a lot of image representation in problem-solving of special angle trigonometric function. The implication of the results of this study is to teach special angle trigonometric function material based on appropriate representations.